An Exploratory Study of the Prevalence and Risk Factors of Hypercholesterolemia Among the Elderly in Kelating Village, Tabanan Regency - Pramesti, AA Intan; Sidemen, Premayani; Wirawan, I Made Suma; Adi Putra, Kadek Nova; R. P, Indry Agatha (Jurnal Sehat Indonesia (JUSINDO), 2025)
Hypercholesterolemia, characterized by elevated levels of LDL, triglycerides, and total cholesterol, is a common but often undetected condition among the elderly. In Indonesia, the prevalence of hypercholesterolemia in individuals aged 65–74 is reported at 38.2%. Early detection is critical to prevent severe complications. Dietary habits and physical inactivity, particularly in populations such as the Segara Santhi elderly group in Kerambitan Village, Tabanan—who have a history of pork consumption and low physical activity—may increase vulnerability to this condition. This preliminary cross-sectional study aimed to explore the prevalence and potential risk factors associated with hypercholesterolemia among elderly individuals in the Segara Santhi group. Using purposive random sampling, 30 elderly participants were selected. Fasting total blood cholesterol levels were measured after an 8-hour fast. Data were analyzed and presented descriptively and in tabular form. A total of 16 participants (51.6%) had total cholesterol levels >200 mg/dL, with a higher proportion observed in elderly women. No statistically significant associations (P>0.05) were found between hypercholesterolemia and gender, age, blood pressure, or fasting blood glucose. However, a significant relationship was identified between hypercholesterolemia and uric acid levels (P<0.05). As a preliminary study, these findings suggest a high prevalence of hypercholesterolemia in this elderly population and indicate a possible link with uric acid levels. Further research with a larger sample size is needed to validate these results and better understand associated risk factors.